Thermal and solutal performance of Cu/CuO nanoparticles on a non-linear radially stretching surface with heat source/sink and varying chemical reaction effects. (December 2021) - Shamshuddin, MD.; Abderrahmane, Aissa; Koulali, Aimad; Eid, Mohamed R.; Shahzad, Faisal; Jamshed, Wasim
Abstract: Current simulations, heat and mass transport of a variable hydromagnetic flow of Copper and Copper oxide-water nanoparticles suspended in nanofluid on a non-linear radially stretching surface in the presence of various impacts have been analyzed. The mathematical model scrutinizes the impacts of thermal radiation, viscous dissipation, and heat source/sink in thermal transport equation and variable chemical reaction in mass transport equation Additionally, velocity slip is imposed in boundary conditions. Further, the impacts of two shapes nanoparticle named column and lamina on the over nonlinearly radially stretched surface. The higher-order equations modeling the problem are mutated into nonlinear ordinary differential equations via similarity transformations approach, while the solutions to the modified equations are sought using Keller Box technique.